(untitled) (Texas Journal of Medical Science, 2023)
To study the structure and antibiotic resistance of pathogens of intraabdominal infections and to evaluate in vitro antibacterial efficacy of polyvalent pyobacteriophage "Sextaphag" on the biomaterial obtained from patients with peritonitis of different etiology